1992
DOI: 10.1002/art.1780350510
|View full text |Cite
|
Sign up to set email alerts
|

Salivary testosterone levels in women with systemic lupus erythematosus

Abstract: Objective. To measure salivary testosterone in women with systemic lupus erythematosus (SLE).Methods. We investigated concentrations of salivary testosterone in 13 women with active SLE and 47 women with inactive SLE, and in 72 healthy female controls.Results. We found a significant decrease in salivary testosterone concentrations in glucocorticoidtreated SLE patients (mean 2 SD 0.06 f 0.04 nmoled liter) but no differences in concentrations in untreated patients (0.09 f 0.03 nmolesfiiter), compared with the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…A study suggested a lower SHBG level in RA patients [ 7 ], while other studies did not support this finding [ 6 , 8 ]. Additionally, it is challenging to determine whether the decreased SHBG levels are caused by RA itself or by glucocorticoid treatment, a common method of treating RA which may result to decreased SHBG level [ 36 ]. Our findings, however, overcame the limitation of these studies and extended prior findings in several important ways.…”
Section: Discussionmentioning
confidence: 99%
“…A study suggested a lower SHBG level in RA patients [ 7 ], while other studies did not support this finding [ 6 , 8 ]. Additionally, it is challenging to determine whether the decreased SHBG levels are caused by RA itself or by glucocorticoid treatment, a common method of treating RA which may result to decreased SHBG level [ 36 ]. Our findings, however, overcame the limitation of these studies and extended prior findings in several important ways.…”
Section: Discussionmentioning
confidence: 99%
“…M. Navarro и соавт. [24] отмечают, что более низкие концентрации ГСПГ у больных РА ассоциируются с терапией ГК, что также согласуется с нашими данными. L. Stafford и соавт.…”
Section: Discussionunclassified